STUDI PENGEMBANGAN KELEMBAGAAN BERDASARKAN KULTUR MASYARAKAT LOKAL PADA KELOMPOK NELAYAN - Ermayanti Ermayanti (Universitas Andalas, 2014)
This article is the result of research on the social institutions that can provide a positive force for the fishermen in their daily lives. Social institutions fishery in this case is able to provide answers to social problems such as poverty. Strengthening social group of fishermen through social institutions is an urgent need and absolutely necessary by fishermen, so they can compete in a conducting fisheries and to improve the welfare of her life. The results showed that traditional institutions are still living in Nagari Tiku Selatan is a ‘kelompok sosial pengajian’, ‘arisan and ‘yasinan’, still running well. Participation of households on social groups is also very good. Almost all of the mothers involved in the routine activities of the group. ‘Pengajian’ and ‘yasinan’ conducted each week in rotation from house to house. While gathering held every two weeks. Social strategy is done by utilizing the social ties that exist in rural areas in the form of local welfare agencies, production relationship to kinship-based social networking or friendship